2021
DOI: 10.1002/lary.29489
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism During Pregnancy Treated With Parathyroidectomy: A Systematic Review

Abstract: Objectives/Hypothesis: The primary objective of this study was to assess the safety of parathyroidectomy during pregnancy as treatment for hyperparathyroidism (HPTH) in comparison to nonsurgical management plans. Secondary outcomes involved analyzing the safety of surgery in the third trimester and the benefit of operating on asymptomatic pregnant patients.Study Design: Systematic review. Methods: PRISMA-guided systematic review of all cases of primary hyperparathyroidism during pregnancy published in peer-rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…39 A recent systematic review found that surgery results in better fetal outcomes, and recommends surgery in the second or third trimester regardless of patient symptomatology. 38 Preoperative localization with ultrasound is safe in any trimester. Recently, the American College of Obstetricians and Gynecologists guidelines for diagnostic imaging in pregnancy have stated that sestamibi scan at doses of less than 5 mGy does not increase the risk of birth defects 42 and thus may be used for parathyroid localization.…”
Section: Special Patient Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…39 A recent systematic review found that surgery results in better fetal outcomes, and recommends surgery in the second or third trimester regardless of patient symptomatology. 38 Preoperative localization with ultrasound is safe in any trimester. Recently, the American College of Obstetricians and Gynecologists guidelines for diagnostic imaging in pregnancy have stated that sestamibi scan at doses of less than 5 mGy does not increase the risk of birth defects 42 and thus may be used for parathyroid localization.…”
Section: Special Patient Populationsmentioning
confidence: 99%
“…The incidence of PHPT in women of childbearing age is eight per 100,000, 37 and although gestational PHPT is estimated to be less than 1%, the true incidence is likely to be higher given the overlap of PHPT and pregnancy symptoms and under-recognition of the disease. 38 In addition to the typical manifestations of PHPT, the consequences of untreated PHPT in pregnancy include hyperemesis gravidarum, preeclampsia, miscarriage, intrauterine growth restriction, and neonatal tetany secondary to fetal parathyroid gland suppression. [37][38][39] Although there are limited data on the treatment of PHPT in pregnancy, a few studies have lent clarity to issues such as medications safe to use in pregnancy and appropriate work-up and surgical management during pregnancy.…”
Section: Special Patient Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on pHPT in pregnancy primarily consists of case reports and retrospective cohort studies; as a result, no conclusive data exist on whether the risks of conservative management outweigh the risks of surgery in pregnancy. A very recent systematic review evaluated 382 cases of gestational hyperparathyroidism and reported parathyroidectomy during pregnancy in 71.7% and non-surgical management in the remaining 28.3% of the cases [43]. The overall infant complication rate was lower when surgery in the second trimester was performed compared with conservative therapy (9.1% vs. 38.9%).…”
Section: Management Of Primary Hyperparathyroidism During Pregnancymentioning
confidence: 99%
“…The overall infant complication rate was lower when surgery in the second trimester was performed compared with conservative therapy (9.1% vs. 38.9%). On the basis of this evidence, the authors concluded that parathyroidectomy is associated with fewer risks and better fetal outcomes than more conservative treatments [43]. A number of experts suggest surgery in the second trimester for all pregnant patients with pHPT regardless of the maternal serum calcium concentrations [19,34,[44][45][46][47].…”
Section: Management Of Primary Hyperparathyroidism During Pregnancymentioning
confidence: 99%